Foreign and domestic policy of the people’s Republic of China during the reign of Hu Jintao (Journal of Philosophy Culture and Political Science, 2018)
Recently, ruling 70 years since the founding of the PRC the rulers of China are considered dividing by generations. The rulers, led by Mao, are the first generation, the leaders under the «architect» of the Chinese economy, Deng Xiaoping – the second, retaining the succession of power and pursuing a successful foreign policy Jiang Zemin – the third, who heads the PRC since 2013 Xi Jinping is regarded as the fifth generation. Each of the generations contributed to the development of the PRC. The article deals with Hu Jintao, leader of the fourth generation of Chinese leaders, who made a great contribution to strengthening the authority of the PRC at the world level. The determination of Hu Jintao’s political personal qualities, the study of China’s foreign and domestic policy, during his rule is a prerequisite for understanding China’s current policy. The article examines the political personality of Hu Jintao, his activities, foreign and domestic policy and continuity in the power of the PRC.Key words: Hu Jintao, PRC, Harmonious world, domestic and foreign policy.